The Effectiveness of Shepherd Leadership and Trust in the School on Teacher’s Work Motivation and Commitment to the School during the COVID-19 Pandemic - Hermawati, Oki; Santosa, Erwin; Bernarto, Innocentius (Sekolah Tinggi Teologi SAAT, 2020)
This research aims to find the effect of shepherd leadership and organizational trust on work motivation and school commitment. This study was directed at Ketapang Christian Schools (SKK), located in Jakarta and Cibubur (West Java). This research used a saturated sample technique, which means the entire population became sample. The total number of respondents is 100. The Partial Least Square Structural Equation Modeling (PLS-SEM) method was selected as a statistical analysis technique. The conclusion showed that shepherd leadership and trust in the school are essential factors that positively impacted teacher’s work motivation. Shepherd leadership and trust in the school also have a positive influence on the commitment to the school. Shepherd leadership has a supportive influence on trust in the school, and work motivation has a supportive impact on the commitment to the school. The finding is expected to provide input for the school in considering policies, especially those related to school organizational structures, to build up trust, work motivation, and teachers’ commitment to the school.